Early neurological complications of coronary artery bypass surgery. Issue 6506 (16th November 1985) - Shaw, P J; Bates, D; Cartlidge, N E; Heaviside, D; Julian, D G; Shaw, D A
Abstract : A prospective study of 312 patients undergoing elective coronary artery bypass surgery was undertaken to determine the incidence, severity, and functional impact of postoperative neurological complications. Detailed evaluation of the patients showed that neurological complications after surgery were common, occurring in 191 of the 312 patients (61%). Although such a high proportion of the total developed detectable changes, serious neurological morbidity was rare. Neurological disorders resulted in death in only one patient (0.3%) and severe disability in only four (1.3%). Forty eight patients were mildly disabled during the early postoperative period, and the remaining 138 with neurological signs had no serious functional disability. The postoperative neurological disorders detected included one death from cerebral hypoxic damage. Prolonged depression of conscious level was observed in 10 patients (3%) and definite stroke in 15 (5%); 78 (25%) developed ophthalmological abnormalities and 123 (39%) primitive reflexes; postoperative psychosis was observed in four (1%); and 37 (12%) developed disorders of the peripheral nervous system. The incidence of serious neurological problems such as fatal cerebral damage, stroke, and brachial plexopathy is in accordance with experience elsewhere. Lesser abnormalities, whose detection required detailed neurological examination, were much commoner than expected from previous reports.